PENGEMBANGAN USAHA MIKRO DIAMOND GLASSYCRAFT KAB KUNINGAN – PROVINSI JAWA BARAT - Angga Sucitra Hendrayana; Imas Maesaroh; Maman Sudirman; Nana Setiana (Jurnal Publika Pengabdian Masyarakat, 2019)
The handicraft business of "Diamond Glassycraft" glass waste is a business that has only been established since 2016 which is still very simple both in terms of production and business management. Products that have been produced from this home-based craft business are still limited to orders and offered Car Free Day events every Sunday, with the production process using simple equipment and simple product packaging. For the management system, the business is run traditionally and there is no definitive and adequate business financial record, everything is still done simply without clear accounting. A marketing system that has not been organized, and the designs of the products are not varied and only rely on orders. The purpose of this community service activity is to provide training on how to make a simple bookkeeping system so that this business can be better organized in terms of administration, make marketing strategies and make more varied product design.Keywords: Micro Business, handicraft business